Gestion des déchets au sein des entreprises, déploiement de l’économie circulaire en Algérie, étude exploratoire - BOUBEKEUR Mohammed; ARGILLOS Amal (Journal of North African Economies, 2025)
This study focuses on waste management within companies for the deployment of the circular economy (CE) in the national economy of Algeria, which is an alternative model of the linear model. an exploration study was made in an Algerian company Algia Telecom(AT) in the field of telecommunications, the analysis of the results shows that AT has an integrated management of their waste ,it ingests the principles related to the CE are the 4R and industrial ecology in cooperation with the national recovery company ENR ,the deployment of CE in Algeria requires inter-company cooperation in community through the adaptation of circular business model whose business ecosystem is the key to the deployment of circular economy practices in Algeria .